Synchronized surface oxygen states and electron-hole passage in microwave-assisted tungsten oxide for photocatalytic organic decomposition and antibacterial activity. Issue 6 (December 2022) - Hwang, In-Seon; Mahadik, Mahadeo A.; Lee, Hyun Hwi; Choi, Sun Hee; Jang, Jum Suk
Abstract: The present study focuses on controlling the composition of microwave-fabricated tungsten oxide (WO3 ) nanoparticles through annealing at 500 °C. The significance of annealing on the surface oxygen states and the photocatalytic performance of WO3 nanoparticles were systematically investigated for the removal of organic pollutants and bacteria. The optimum photocatalyst, microwave-assisted WO3 which was successively annealed for 6 h and Pt-loaded (Pt/WO3 -M-6 h) demonstrated high photocatalytic performances in inactivation (99 %) against E. coli and S. aureus as well as in degradations of Orange II dye (93 %) and BPA (99 %) under one sun illumination for 180 min. The integration of WO3 -M-6 having a moderate amount of surface oxygen defects and Pt loading could provide the most favorable environment in charge transfer by reducing the electron-hole recombination and as an electron collector, respectively. Detailed mechanisms have been proposed for the photocatalytic decomposition of organic pollutants and the photocatalytic disinfection of waterborne bacteria. Graphical Abstract: Here, for the first time, we focused on the relation between crystalline structure and photocatalytic performance of surfactant-free microwave-assisted WO3 nanoarchitectures. The optimum Pt/WO3 -M-6 h exhibited 93 % and 99 % degradation for orange II dye and BPA decomposition in 180 min. Additionally, the antibacterial activities of Pt/WO3 -MW-6 h photocatalyst against Gram-negative and Gram-positive bacteria were systematically investigated without any surfactants. ga1 Highlights: WO3 nanoarchitectures were developed via a simple surfactant-free microwave- process. Correlation between crystalline structure and photocatalytic performance of WO3 nanoarchitectures was studied in detail. Pt/WO3 -M-6 h exhibited 93 % orange II dye and 99 % BPA decomposition efficiency within 180 min 99 % PC antibacterial activity was achieved for optimum Pt/WO3 -M-6 h photocatalyst. Two charge transfer processes during organic decomposition and E. coli inactivation are well proposed.